Electrooxidation of sulfide by cobalt pentacyanonitrosylferrate film on glassy carbon electrode by cyclic voltammetry - Paim, Leonardo L. [UNESP]; Stradiotto, Nelson Ramos [UNESP] (Pergamon-Elsevier B.V. Ltd, 2010)
A glassy carbon (GC) electrode was modified with cobalt pentacyanonitrosylferrate (CoPCNF) film. Cyclic voltammetry (CV) of the CoPCNF onto the GC (CoPCNF/GC) shows a redox couple (Fe(III)/Fe(II)) with a standard potential (E(0)') of 580 mV. The current ratio I(pa)/I(pc), remains almost 1, and a peak separation (Delta E(p)) of 106 mV is observed in 0.5 M KNO(3) as the supporting electrolyte. Anodic peak currents were found to be linearly proportional to the scan rate between 10 and 200 mVs(-1), indicating an adsorption-controlled process. The redox couple of the CoPCNF film presents an electrocatalytic response to sulfide in aqueous solution. The analytical curve was linear in the concentration range of 7.5 x 10(-5) to 7.7 x 10(-4) M with a detection limit of 4.6 x 10(-5) M for sulfide ions in 0.5 M KNO(3) solution. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Sulfide; Cobalt pentacyanonitrosylferrate; Cyclic voltammetry; Modified electrode